A comprehensive study of common and rare genetic variants in spermatogenesis-related loci identifies new risk factors for idiopathic severe spermatogenic failure - Guzmán-Jiménez, Andrea (2024)
Funding Information: This work was supported by the Spanish Ministry of Science and Innovation through the Spanish National Plan for Scientific and Technical Research and Innovation (PID2020-120157RB-I00) and the Andalusian Government through the research projects of 'Plan Andaluz de Investigaci\u00F3n, Desarrollo e Innovaci\u00F3n (PAIDI 2020)' (ref. PY20_00212) and 'Proyectos de Investigaci\u00F3n aplicada FEDER-UGR 2023' (ref. C-CTS-273-UGR23). S.G.-M. was funded by the previously mentioned projects (ref. PY20_00212 and PID2020-120157RB-I00). A.G.-J. was funded by MCIN/AEI/10.13039/501100011033 and FSE 'El FSE invierte en tu futuro' (grant ref. FPU20/02926). IPATIMUP integrates the i3S Research Unit, which is partially supported by the Portuguese Foundation for Science and Technology (FCT), financed by the European Social Funds (COMPETE-FEDER) and National Funds (projects PEstC/SAU/LA0003/2013 and POCI-01-0145-FEDER-007274). S.S. is supported by FCT funds (10.54499/DL57/2016/CP1363/CT0019), ToxOmics-Centre for Toxicogenomics and Human Health, Genetics, Oncology and Human Toxicology, and is also partially supported by the Portuguese Foundation for Science and Technology (UIDP/00009/2020 and UIDB/00009/2020). S. Larriba received support from Instituto de Salud Carlos III (grant: DTS18/00101), co-funded by FEDER funds/European Regional Development Fund (ERDF) - a way to build Europe) and from 'Generalitat de Catalunya' (grant 2021SGR052). S. Larriba is also sponsored by the 'Researchers Consolidation Program' from the SNS-Dpt. Salut Generalitat de Catalunya (Exp. CES09/020). All authors declare no conflict of interest related to this study. We thank the National DNA Bank Carlos III (University of Salamanca, Spain) for supplying the control DNA samples of the Iberian replication cohort and all the participants for their essential collaboration. Also, we thank to Servier Medical Art (licensed by Creative Commons Attribution 4.0 License: https://creative commons.org/licenses/by/4.0/) and BioRender (through individual license at https://app.biorender.com) for providing some elements used in Figs 1, 2, and 3. This article is related to the PhD Doctoral Thesis of Andrea Guzm\u00E1n-Jim\u00E9nez. Funding for open access charge: Universidad de Granada / CBUA. Funding Information: Spanish Ministry of Science and Innovation through the Spanish National Plan for Scientific and Technical Research and Innovation (PID2020-120157RB-I00) and the Andalusian Government through the research projects of \u2018Plan Andaluz de Investigaci\u00F3n, Desarrollo e Innovaci\u00F3n (PAIDI 2020)\u2019 (ref. PY20_00212) and \u2018Proyectos de Investigaci\u00F3n aplicada FEDER-UGR 2023\u2019 (ref. C-CTS-273-UGR23). S.G.-M. was funded by the previously mentioned projects (ref. PY20_00212 and PID2020-120157RB-I00). A.G.-J. was funded by MCIN/AEI/10.13039/501100011033 and FSE \u2018El FSE invierte en tu futuro\u2019 (grant ref. FPU20/02926). IPATIMUP integrates the i3S Research Unit, which is partially supported by the Portuguese Foundation for Science and Technology (FCT), financed by the European Social Funds (COMPETE-FEDER) and National Funds (projects PEstC/SAU/LA0003/2013 and POCI-01-0145-FEDER-007274). S.S. is supported by FCT funds (10.54499/DL57/2016/CP1363/CT0019), ToxOmics-Centre for Toxicogenomics and Human Health, Genetics, Oncology and Human Toxicology, and is also partially supported by the Portuguese Foundation for Science and Technology (UIDP/00009/2020 and UIDB/00009/2020). S. Larriba received support from Instituto de Salud Carlos III (grant: DTS18/00101), co-funded by FEDER funds/European Regional Development Fund (ERDF)\u2014a way to build Europe and from \u2018Generalitat de Catalunya\u2019 (grant 2021SGR052). S. Larriba is also sponsored by the \u2018Researchers Consolidation Program\u2019 from the SNS-Dpt. Salut Generalitat de Catalunya (Exp. CES09/020). Publisher Copyright: © 2024 The Author(s).